VALUASI HUTAN WISATA KOTA DUMAI PROPINSI RIAU - Abdillah, Nuryasin; Mubarak, Mubarak; Thamrin, Thamrin (Bumi Lestari Journal of Environment; Vol 11 No 2 (2011), 2011)
The research results shown that the direct use value consist of economic value of woods in the Resort forest of Dumai for bandwidth of 3.298 acres is Rp 8.649.994.400. With the value NPV within 25 years is Rp 78.454.488.312,11. Economic value of cordwood itself within 1 year is Rp 388.756.500. While the economic value within 25 years is Rp 3.466.901.293,70. The economic value of decorated plants is Rp 608.415.040, with NPV within 25 years is Rp 5.495.376.545,72-. The economic value of fauna is 330.030.000,-, Value NPV within the next 25 years is Rp 1.109.457.677. The economic value of medicine plants within 25 years (NPV) is Rp 10.043.360.612,61. Meanwhile indirect use value which is consist of economic value of carbon absorption of the forest is Rp 51.824.772.000, Value of NPV within 25 years from that carbon absorption is Rp 470.388.298.259,56 and the economic value of the existence forest of Dumai is Rp 49.266.513.000,-. The value of existence forest of Dumai within 25 years with discount factor 10% is Rp 447.148.724.859,53. Total economic value resort forest of Dumai is Rp.112,177,938,617 and Value NPV within 25 years with assumption steady price and with rate of interest 10% is Rp.1,017,970,152,600. The result of this research hopefully could give information to the people who live near the forest, so they have motivated to maintain their forest existence. Therefore, it is necessary to do some social activity about existence, use and benefit of the forest. While could be observe from social wise, culture wise, economic wise or ecology wise to all kind of people even to those whose is not indirect interaction to the forest but also to the people whose indirect use to the benefit of those forest.
Keywords: economic valuation, resort forest Dumai, benefit, productivity, contingent